2009
DOI: 10.1002/smj.762
|View full text |Cite
|
Sign up to set email alerts
|

Managing liquidity in research‐intensive firms: signaling and cash flow effects of patents and alliance activities

Abstract: The effective holding and management of liquid assets is critical to success in research‐intensive industries. The primary output of invention is new knowledge. However, because of its ‘sticky’ characteristics, knowledge may not easily diffuse to external shareholders, leading to knowledge asymmetries between managers/employees and external suppliers of capital. Many valuable R&D projects may thus fail to attract external financing, limiting a firm's ability to invest in R&D. In this study, we examine how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 65 publications
2
75
0
1
Order By: Relevance
“…A robust patent regime (such as that available to the bio-pharmaceutical industry) enables entrepreneurial firms to convert their research innovations into a valuable resource that can be commercialized via out-licensing (Levitas and McFadyen, 2009). Recent research has demonstrated the link between patent citations and the market value of a patent (Nair et al, 2011).…”
Section: Market Imperfection and Information Asymmetry: Social Statusmentioning
confidence: 99%
“…A robust patent regime (such as that available to the bio-pharmaceutical industry) enables entrepreneurial firms to convert their research innovations into a valuable resource that can be commercialized via out-licensing (Levitas and McFadyen, 2009). Recent research has demonstrated the link between patent citations and the market value of a patent (Nair et al, 2011).…”
Section: Market Imperfection and Information Asymmetry: Social Statusmentioning
confidence: 99%
“…The liquidity of such firms, when they are listed, may be reduced compared to other sectors that are easier to understand for a large public of investors (MANGEMATIN et al, 2003;LEVITAS;MCFADYEN, 2009).…”
Section: Economic Position (Ep)mentioning
confidence: 99%
“…Thus R&D investment provides a very low inside collateral value which makes raising funds externally more costly for R&D projects than for other types of investments (Arrow, 1962;Berger and Udell, 1998;Harhoff, 1998). Thus, firms willing to pursue an ambitious R&D agenda may face serious difficulties to attract external investors or to obtain bank loans and may therefore pile up cash to finance their R&D. This leads to a trade-off between investing in current R&D projects and retaining cash for future ones (Levitas and McFadyen, 2009). …”
Section: Financial Constraints and The Nature Of Randdmentioning
confidence: 99%
“…More recently, Levitas and McFadyen (2009) who also study biotechnology firms in the U.S., find that the nature of the collaboration matters. Certain alliance activities -in particular with the aim of "exploitation" -provide important signaling mechanisms and thus lower the firms' need to hold liquid assets to finance their R&D activities.…”
Section: Collaboration and Liquidity Constraintsmentioning
confidence: 99%